2015
DOI: 10.1177/1203475415622207
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-OH Vitamin D Level in Psoriatic Patients and Comparison With Control Subjects

Abstract: Most of the patients with psoriasis had vitamin D deficiency, which may have contributed to the evolution of their psoriasis. However, considering the high prevalence of vitamin D deficiency in Iran, no difference was noted between the psoriatic patients and the controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 24 publications
4
32
2
1
Order By: Relevance
“…In epidermal keratinocytes, the intrinsic danger signals cytosolic DNA and the antimicrobial peptide psoriasin (S100A7) were identified as disease-relevant triggers for caspase-5 activity and IL-1β production in a Th1/Th17 environment. Patients suffering from psoriasis have lower vitamin D levels [32], and we observed that application of vitamin D suppresses caspase-5 in keratinocytes in psoriasis. Current studies link IL-1β production and Th17-mediated effects in autoimmune diseases, including psoriasis, and these observations could contribute to the developing understanding of their pathogenesis and therapeutic interference [2, 33, 34].…”
Section: Discussionmentioning
confidence: 91%
“…In epidermal keratinocytes, the intrinsic danger signals cytosolic DNA and the antimicrobial peptide psoriasin (S100A7) were identified as disease-relevant triggers for caspase-5 activity and IL-1β production in a Th1/Th17 environment. Patients suffering from psoriasis have lower vitamin D levels [32], and we observed that application of vitamin D suppresses caspase-5 in keratinocytes in psoriasis. Current studies link IL-1β production and Th17-mediated effects in autoimmune diseases, including psoriasis, and these observations could contribute to the developing understanding of their pathogenesis and therapeutic interference [2, 33, 34].…”
Section: Discussionmentioning
confidence: 91%
“…Thus, 12 articles, comprising 571 patients with psoriasis and 496 HCs, met the inclusion criteria [5][6][7][8][9][10][11][12][13][14][15][16] ( Table 1). The patients had not been exposed to any drug previously in the studies, there were no patient populations with psoriatic arthritis except in one study, 6 and none of the patients had taken oral corticosteroids that might induce osteopenia/osteoporosis. Except for one, 15 studies did not mention which type of psoriasis (chronic plaque, guttate, palmoplantar, scalp) was considered.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…4 However, studies that have compared circulating 25 (OH)D levels between patients with psoriasis and healthy controls (HCs) and determined the relationship between 25(OH)D levels and psoriasis severity have reported inconsistent results. [5][6][7][8][9][10][11][12][13][14][15][16] To overcome the limitations of individual studies and resolve inconsistencies, we performed a metaanalysis, comparing the serum/plasma 25(OH)D levels between patients with psoriasis and HCs, and evaluated the correlation of these levels with disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D plays a critical role in psoriasis, and this is evidenced in many studies which reported either a deficiency or insufficiency of serum vitamin D in psoriatic patients [59,60,61]. Several case-control studies have shown significant lower levels of serum 25(OH)D in psoriatic patients compared to controls and reported an inverse correlation between serum 25(OH)D and the severity of the disease [62,63,64,65,66].…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%